Influence of graphene nanoplatelets (GNPs) on mode I fracture toughness of an epoxy adhesive under thermal fatigue. Issue 19 (18th October 2017) - Mohamed, M.; Taheri, F.
Abstract: The contribution of graphene nanoplatelets (GNPs) for enhancing the fracture toughness of a commonly used room-cured epoxy, used to bond E-glass/epoxy composite adherends, is evaluated. A comprehensive experimental investigation is conducted to examine the performance and degradation of adhesively bonded joints subject to cyclic thermal loading using the standard double cantilever beam (DCB) specimens. Several groups of DCB specimens were fabricated using the adhesive reinforced with four different GNPs weight-percentages (i.e. 0.0, 0.25, 0.5 and 1%). The specimens are subsequently subjected to various numbers of thermal cycles (to a maximum of 1000 heating/cooling cycles), and then tested, and the resulting mode I fracture toughness values are evaluated and compared. The extent and modes of damage captured through microscopy and scanning electron microscopy images are presented and discussed. In addition, a computational framework, using the cohesive zone modeling technique, is developed for predicting the response of the adhesives and their damage evolution.